PENERAPAN PROGRAM CORPORATE SOCIAL RESPONSIBILITY PADA THE OBEROI BEACH RESORT BALI - MADE AYU ARINDA SARASWATI; KASIANI KASIANI; I MADE WIDIANTARA; ISTIARTO ISTIARTO (GANEC SWARA, 2020)
Corporate Social Responsibility (CSR) is an obligation of employers to formulate policies, make decisions, or follow the desired line of action in terms of community goals and values that emphasize on corporate responsibility which is no longer just an economic activity (creating profit for business continuity), yet social responsibility including the environment. This study uses qualitative data with descriptive methods. Data obtained by observing the object of research, conducting interviews with the Human Resources Department, employees, and the community around the hotel and documentation of CSR activities at The Oberoi Beach Resort Bali. The purpose of this study is to find out the steps of CSR implementation, types, and implementation of CSR and the problem with the solutions related to the implementation of CSR in The Oberoi Beach Resort Bali. The results of this study are The Oberoi Beach Resort Bali implements the steps of CSR implementation, such as planning, implementing, and reporting. The implementation of CSR activities is based on the implementation of CSR in Indonesia, such as CSR based on charity philanthropy and social activity.